Fun School Movements Play a Crucial Role in Improving the Socio-Emotional Well-Being of Students - Aprillia Fentika Dewi Gita Anggraeni; Shahzadi Hina (Al-Qalam Institue, 2024)
The Fun School Movement plays a role in improving students' socio-emotional well-being. This study highlights the growing importance of a supportive and engaging school environment, as students' emotional and social well-being is crucial to their overall development. This study underlines the importance of the Fun School Movement in promoting a balanced and healthy learning environment, which can serve as a model for other schools aiming to improve their students' socio-emotional well-being. The purpose of this study was to examine how the implementation and impact of the Fun School Movement in improving students' socio-emotional well-being. This study used a descriptive qualitative method, focusing on observation, interviews, and documentation with data analysis according to Miles and Huberman. The findings of the study revealed that a fun school environment plays an important role in fostering a sense of security, belonging, and happiness, which significantly affect students' emotional and motivational states. The role of teachers as emotional companions has been shown to be important in providing support and guidance, helping students overcome personal and academic challenges. Parental involvement has been shown to strengthen the bond between home and school, which further supports students' well-being. The findings are expected to contribute to the understanding that students' holistic development depends not only on academic achievement but also on emotional support and social engagement.